Insects: a big fold-n-flap book - Reasoner, Charles; Doherty, Paula (Linde, New Jersey Just For Kids, 2009)
Kids will enjoy different insects and other surprises in this large format FOLD-N-FLAP book.
Keywords: Insects - oversize books; Picture books for children